Intensity and distribution of Meloidogyne Spp. in cowpea growing areas of Mozambique - Kisitu, J.; Janssen, T.; Chiulele, R.M.; Mondjana, A.M.; Coyne, Danny L. (2017)
Cowpea (Vigna unguiculata (L.) Walp.) is an important food crop in Mozambique. The crop is cultivated almost exclusively by smallholder farmers in warm marginal environments of the country. Rootknot nematodes (Meloidogyne spp.) are among the major constraints limiting cowpea yield in the country. Understanding rootknot nematode prevalence, distribution and damage intensity in major cowpea growing areas is crucial in making control decisions. A study was conducted to identify rootknot nematode species, determine prevalence, distribution and damage intensity (incidence and severity) in Mozambique. The study covered 8 districts belonging to 3 provinces namely: Gaza, Inhambane, and Nampula provinces. Out of the 72 cowpea fields surveyed, 56.9% were infested with rootknot nematodes. Inhambane province registered the highest root knot nematode prevalence at 74%. Meloidogyne incognita and M. javanica were the most frequent root knot nematode species encountered. M. enterolobii was another species observed to be associated with cowpea rootknot in this study. The highest frequency of M. incognita and M. javanica was observed in cowpea fields from Inhambane and Gaza provinces, respectively. Provinces differed significantly in terms of the intensity of rootknot nematode damage in which Inhambane province recorded the highest rootknot incidence and galling severity at 39.8% and 1.9, respectively. Rootknot nematode damage intensity differed significantly across districts in which Homoine district registered the highest rootknot nematode incidence and galling severity at 55.8% and 2.1, respectively.